Rhodium-Catalysed Hydroboration of Terminal Alkynes Using Pinacolborane Promoted by Tri(2-furyl)phosphine - Wang, Kongchen; Bates, Roderick W. (Synthesis, 2017)
Tri(2-furyl)phosphine is a superior ligand to triphenylphosphine in the rhodium-catalysed hydroboration of alkynes with pinacolborane to yield alkenylboronates. In general the reactions are faster and the products are cleaner.
Keywords: boronate; hydroboration; catalysis; rhodium; phosphine